Program Magang Modul Penggunaan Sistem Point Of Sales Dalam Memudahkan Perekapan Penjualan PT Olsera Indonesia Pratama - Mon, Muhammad Donal; Jackson (Pakis Journal Institute, 2024)
Olsera Indonesia Pratama, which has the Olsera brand, is a startup company that operates in the point of sales sector. The Point of Sales system is an innovative system that makes it easier for people to carry out business transactions. PT Olsera is a technology-based company. This company is called technology-based because it uses a system supported by cloud storage. Olsera sells a system to help MSMEs in Indonesia but does not use it in the company's own operational activities. Olsera has a lot of work done manually. such as sales recording which is only done using Excel. If done manually continuously, work effectiveness will decrease and a lot of time will be wasted. This internship activity was carried out to assist Olsera's finance team in carrying out recording using a point of sales system so that the work carried out could be more effective and efficient. This internship activity is carried out by means of observation and interviews. The results of implementing the use of the system are that the finance team's activities become more efficient and effective, reducing company expenses, more effective financial control and faster financial reporting.